Biomass Estimation of Brantas Riparian Zone Tree, Batu City, East Java - Hamdani Dwi Prasetyo; Ari Hayati (UIN Sunan Gunung Djati Bandung, 2025)
Research to estimate carbon absorption using ecosystem productivity models carried out in riparian zones is still rare. This research aims to determine the carbon and biomass potential in the Brantas River riparian zone, Batu City. The data obtained was retrieved using Microsoft Excel 2013 software. The data was tested differently using Paleontological Statistics, through normality and homogeneity tests, and continued with a different test. Different tests are carried out to determine the quality of the riparian zone between the observation stations. In addition, the Principal Component Analysis (PCA) is continued with Biplot and Cluster Analysis to understand the differences between the stations and to know the characteristics between stations. The biomass in the village of Sidomulyo is bigger than any other location. The biomass is about 8760 tons/ha with a carbon potential of 4380 tons. This value is very high compared to the entire location. The average potential carbon at each location ranges from 67 to 285 tons. Sidomulyo village's riparian zone, rich in carbon and biomass, requires preservation to prevent global warming due to carbon emissions. The closure of land at the site of the village of Sidomulyo did not cause the riparian zone in the village to become less. The results showed that although the village of Sidomulyo has a savage land cover and settlements, the carbon storage from trees in the riparian zone is huge. This research aids in developing conservation strategies for riparian zones with high carbon storage potential, supports climate change mitigation, and informs policymakers on sustainable land management practices in the Brantas River watershed.